Enhanced thermoelectric performance of electrochemically deposited cellulose nanofiber-bismuth telluride nanocomposite - Toan, Nguyen Van; Jianghan, Tian; Keit, Sakakibara; Thi Kim Tuoi, Truong; Samat, Khairul Fadzli; Dang Khoa Tran, Ngoc; Van Hieu, Nguyen; Ono, Takahito (IOP Publishing Ltd, 2025)
Thermoelectric generators (TEGs) provide an innovative approach to converting waste heat into electricity. However, practical application of TEGs is constrained by the limited thermoelectric performance of traditional materials like bismuth telluride (Bi2Te3)-based thermoelectric materials. Thick thermoelectric films frequently suffer from cracking, leading to reduced reliability and efficiency. To overcome these limitations, this study investigates the incorporation of cellulose nanofibers (CNF) into Bi2Te3-based thermoelectric films. CNF, a sustainable and biodegradable material, was hypothesized to improve thermoelectric performance by reducing thermal conductivity through enhanced phonon scattering while maintaining favorable electrical conductivity and Seebeck coefficient. Crack-free CNF-Bi2Te3 composite films (400 μm thick) were synthesized using a pulsed electrodeposition method. Structural analysis confirmed that CNF introduced significant microstructural improvements, including grain refinement, enhanced grain boundary scattering, and optimized carrier transport pathways. At an optimal CNF concentration of 0.06 wt%, the ZT value of the composite films reached 0.76, representing a 625% improvement over the pure Bi2Te3 film. This remarkable enhancement was achieved through a significant reduction in thermal conductivity and balanced improvements in electrical conductivity and the Seebeck coefficient. These results highlight the potential of CNF as an effective additive for improving both the thermoelectric efficiency and structural integrity of Bi2Te3-based materials.